2019
DOI: 10.1027/2151-2604/a000355
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Individual Value Change in Adulthood

Abstract: Abstract. Values guide people in their lives as overarching principles of judgments and decision making. Focusing on Schwartz’s circumplex value model, the present work is the first systematic literature review (SLR) to comparatively synthesize the empirical evidence regarding stability and change of values in adulthood. Besides understanding the extent of value change, the aim of this review is to reveal the conditions under which values change. The search procedure and screening revealed 19 publications repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 37 publications
1
21
0
1
Order By: Relevance
“…Values are usually found to be largely stable (Schuster et al, 2019), and this pattern was evident in our study as well. The rank order stability of values was quite high throughout the study (see OSM Table S2C).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Values are usually found to be largely stable (Schuster et al, 2019), and this pattern was evident in our study as well. The rank order stability of values was quite high throughout the study (see OSM Table S2C).…”
Section: Discussionsupporting
confidence: 87%
“…Values are usually quite stable (reviewed in Schuster et al, 2019) over time. However, in the face of threats posed by the COVID-19 pandemic, we found that people's values changed in a direction that implies adjustment to the new life situation, in line with values theory and evolutionary predictions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…been found to be relatively stable, with research showing little change throughout adulthood (Schuster et al, 2019). Moreover, values are thought to transcend specific situations and contexts (Schwartz, 1992).…”
mentioning
confidence: 99%